Terapi non farmakologi rebusan daun sirih hijau untuk mengatasi keputihan pada wanita - Yuliana, Erma (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2024)
BackgroundThe green betel leaf plant is known for its natural antiseptic properties, making it a promising candidate for non-pharmacological therapy in treating vaginal discharge. This study aims to evaluate the effectiveness of boiled green betel leaf extract in managing vaginal discharge among women in the working area of Salembaran Jaya Public Health Center, Rawa Burung Village, Kosambi District, Tangerang Regency, in 2023. MethodsThis research employed a quasi-experimental design with two groups: an intervention group and a control group. The independent variable was the administration of boiled green betel leaf extract, while the dependent variable was the occurrence of vaginal discharge. A total of 138 respondents were involved, evenly divided into 69 participants in each group. Data were analyzed using the Chi-square statistical test. ResultsThe statistical analysis revealed an Asymp. Sig (2-tailed) value of 0.00. Since this value is less than 0.05, the alternative hypothesis is accepted. This indicates a significant difference between the intervention and control groups in the treatment of vaginal discharge. Thus, boiled green betel leaf extract is proven to be effective in addressing vaginal discharge in women. Conclusion and RecommendationsBoiled green betel leaf extract can be considered a viable non-pharmacological treatment option for vaginal discharge. The findings of this study are expected to serve as a reference for women experiencing this condition, encouraging the use of green betel leaf decoction as a natural and safe remedy.